2021
DOI: 10.1049/hve2.12119
|View full text |Cite
|
Sign up to set email alerts
|

Streamer‐to‐precursor transition in N 2 –SF 6 mixtures under positive repetitive submicrosecond pulses

Abstract: The evolution of discharge dynamics in N 2 -SF 6 mixtures under long-term repetitive submicrosecond pulses is investigated based on pulse-sequence resolved electrical and optical diagnostics. The effects of gas pressure, pulse repetition frequency (PRF), and SF 6 concentration on discharge evolutions are determined. The number of applied pulses before breakdown is shown to non-linearly decrease with increasing PRF for all included gas pressures and SF 6 concentrations. A higher SF 6 concentration is favourable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The same streamers were observed in Refs. [12,18,19,22,25,26,38,44,46,[49][50][51][62][63][64][65][66]. It is seen that the streamer diameter can reach the order of the length of the interelectrode distance d. Figure 2c shows that the streamer front moves in the direction of the grounded electrode at different velocities as in our previous studies [51,67].…”
Section: Positive Streamers In Air and Nitrogen At Various Pressures ...supporting
confidence: 61%
See 1 more Smart Citation
“…The same streamers were observed in Refs. [12,18,19,22,25,26,38,44,46,[49][50][51][62][63][64][65][66]. It is seen that the streamer diameter can reach the order of the length of the interelectrode distance d. Figure 2c shows that the streamer front moves in the direction of the grounded electrode at different velocities as in our previous studies [51,67].…”
Section: Positive Streamers In Air and Nitrogen At Various Pressures ...supporting
confidence: 61%
“…The same streamers were observed in Refs. [12, 18, 19, 22, 25, 26, 38, 44, 46, 49–51, 62–66]. It is seen that the streamer diameter can reach the order of the length of the interelectrode distance d .…”
Section: Resultsmentioning
confidence: 99%
“…However, many experimental and simulation results have demonstrated that the NRP discharge regime is not consistent although voltage waveforms in a pulse train are fixed [10,[19][20][21][22][23]. One representative example is the 'corona-to-spark' transition under repetitive pulses concerned by the high-voltage insulation design [19,24]. Complicated discharge regime transitions undermine the consistency of plasma parameters and cause discharge control complexities.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of oxygen addition on production of reactive species have been extensively discussed. However, evolutions of streamer developments (e.g., primary and secondary streamers [34,35]) under long-term repetitive pulses in electronegative gas mixtures at high pressure have not been thoroughly elucidated.…”
Section: Introductionmentioning
confidence: 99%